Endurance - Magee, David (J. Wiley & Sons, 2005)
9 parts: Following Dreams (and Talent); beating the pros; managing high expectations; facing a lurking tiger; dealing with defeat; setting priorities; enduring tough times; mastering the moment; savoring victory